2023
DOI: 10.3390/cancers15184630
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health Data Improve the Prediction of Cardiac Outcomes in Females with Breast Cancer

Nickolas Stabellini,
Jennifer Cullen,
Justin X. Moore
et al.

Abstract: Cardiovascular disease is the leading cause of mortality among breast cancer (BC) patients aged 50 and above. Machine Learning (ML) models are increasingly utilized as prediction tools, and recent evidence suggests that incorporating social determinants of health (SDOH) data can enhance its performance. This study included females ≥ 18 years diagnosed with BC at any stage. The outcomes were the diagnosis and time-to-event of major adverse cardiovascular events (MACEs) within two years following a cancer diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“… 19 , 20 While CVD development is multifactorial, recent evidence suggests that adverse social determinants of health are an important factor in this equation and are linked to a heightened risk of CVD. 21 , 22 , 34 Adverse social determinants of health are also believed to increase chronic stress. 35 Our results support that the association between AL and MACE is also valid for patients diagnosed with BC, LC, or CRC, which are, together with prostate cancer, the top 4 newly diagnosed cancers in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 19 , 20 While CVD development is multifactorial, recent evidence suggests that adverse social determinants of health are an important factor in this equation and are linked to a heightened risk of CVD. 21 , 22 , 34 Adverse social determinants of health are also believed to increase chronic stress. 35 Our results support that the association between AL and MACE is also valid for patients diagnosed with BC, LC, or CRC, which are, together with prostate cancer, the top 4 newly diagnosed cancers in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The study setting was the UH Seidman Cancer Center (Northeast Ohio, US), a tertiary care center that serves urban, suburban, and rural areas, comprising an integrated network of 23 hospitals, >50 health centers and outpatients facilities, and >200 physicians’ offices in 16 counties throughout the region. 21 , 22 Data were obtained from the UH repository, which consists of an open‐source, web‐based cancer data management system that integrates disparate sources of data. 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 The information obtained was complemented with electronic health record information captured via the Electronic Medical Record Search Engine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies evaluating the impact of including SDOH into predictive model performance have resulted in mixed results [5][6][7][8][9][10][11]. Hammond et al [5] demonstrated that adjusting for SDOH improved the accuracy of cardiovascular hospitalization and mortality regression prediction models.…”
Section: Introductionmentioning
confidence: 99%